Amidoligases with ATP-grasp, glutamine synthetase-like and acetyltransferase-like domains: synthesis of novel metabolites and peptide modifications of proteins - Iyer, Lakshminarayan M. (2009)
Recent studies have shown that the ubiquitin system had its origins in ancient cofactor/amino acid biosynthesis pathways. Preliminary studies also indicated that conjugation systems for other peptide tags on proteins, such as pupylation, have evolutionary links to cofactor/amino acid biosynthesis pathways. Following up on these observations, we systematically investigated the non-ribosomal amidoligases of the ATP-grasp, glutamine synthetase-like and acetyltransferase folds by classifying the known members and identifying novel versions. We then established their contextual connections using information from domain architectures and conserved gene neighborhoods. This showed remarkable, previously uncharacterized functional links between diverse peptide ligases, several peptidases of unrelated folds and enzymes involved in synthesis of modified amino acids. Using the network of contextual connections we were able to predict numerous novel pathways for peptide synthesis and modification, amine-utilization, secondary metabolite synthesis and potential peptide-tagging systems. One potential peptide-tagging system, which is widely distributed in bacteria, involves an ATP-grasp domain and a glutamine synthetase-like ligase, both of which are circularly permuted, an NTN hydrolase fold peptidase and a novel alpha helical domain. Our analysis also elucidates key steps in the biosynthesis of antibiotics such as friulimicin, butirosin and bacilysin and cell surface structures such as capsular polymers and teichuronopeptides. We also report the discovery of several novel ribosomally synthesized bacterial peptide metabolites that are cyclized via amide and lactone linkages formed by ATP-grasp enzymes. We present an evolutionary scenario for the multiple convergent origins of peptide ligases in various folds and clarify the bacterial origin of eukaryotic peptide-tagging enzymes of the TTL family.